Effect of the use of earplugs and eye mask on the quality of sleep in intensive care patients: a systematic review - Locihová, Hana; Axmann, Karel; Padyšáková, Hana; Fejfar, Jakub (Journal of sleep research, 2018)
Intensive care unit (ICU) environment has a very strong and unavoidable negative impact on patients' sleep. Sleep deprivation in ICU patients has been already studied and negative effects on their outcome (prolonged ICU stay, decreased recovery) and complication rates (incidence of delirium, neuropsychological sequels of critical illness) discussed. Several interventions potentially improving the sleep disturbance in ICU (sleep-promotion strategies) have been assumed and tested for clinical practice. We present a review of recent literature focused on chosen types of non-pharmacological interventions (earplugs and eye mask) analysing their effect on sleep quality/quantity. From the total amount of 82 papers found in biomedical databases (CINAHL, PubMed and SCOPUS) we included the 19 most eligible studies meeting defined inclusion/exclusion criteria involving 1 379 participants. Both experimental and clinical trials, either ICU and non-ICU patient populations were analysed in the review. Most of the reviewed studies showed a significant improvement of subjective sleep quality when using described non-pharmacological interventions (objective parameters were not significantly validated). Measuring the sleep quality is a major concern limiting the objective comparison of the studies' results since non-standardised (and mainly individual) tools for sleep quality assessment were used. Despite the heterogeneity of analysed studies and some common methodological issues (sample size, design, outcome parameters choice and comparison) earplugs and eye mask showed potential positive effects on sleep quality and the incidence of delirium in ICU patients.
Keywords: delirium; Eye Protective Devices; quality of sleep; Sleep Wake Disorders; spánek; Intensive Care Units; poruchy spánku a bdění; Sleep; péče o pacienty v kritickém stavu; Critical Care; spánková deprivace; earplugs; Delirium; intensive care unit; ochranné prostředky očí; Randomized Controlled Trials as Topic; Humans; chrániče sluchu; jednotky intenzivní péče; Ear Protective Devices; Sleep Deprivation; eye mask; randomizované kontrolované studie jako téma; hospitalisation; lidé